Novel insights into the aetiology of granulomatosis with polyangiitis—a case–control study using the Clinical Practice Research Datalink. (26th February 2018) - Pearce, Fiona A; Lanyon, Peter C; Watts, Richard A; Grainge, Matthew J; Abhishek, Abhishek; Hubbard, Richard B
Abstract: Objectives: We aimed to provide insights into the aetiology of granulomatosis with polyangiitis (GPA), by conducting a large case–control study using a general population-based, prospectively collected database of healthcare records. Methods: We compared all incident cases of GPA in the Clinical Practice Research Datalink 1990–2014, with up to 10 age-, sex- and general practice-matched controls. We identified potential risk factors, recorded numbers of cases and controls exposed to each, and calculated odds ratios (ORs) using conditional logistic regression. Our main analysis excluded data recorded during 1 year before diagnosis, to prevent early symptoms being mistaken for risk factors. Results: We identified 757 people with GPA and matched 7546 controls. People with GPA were five times more likely to have a previous diagnosis of bronchiectasis (OR = 5.1, 95% CI: 2.7, 9.4; P < 0.0001), and these effects remained stable in diagnoses recorded >5 years prior to diagnosis. People with GPA were two to three times more likely than controls to have previous diagnoses of autoimmune diseases or chronic renal impairment, and these effects also remained stable >5 years prior to diagnosis. People with GPA were more likely to have a diagnosis of pulmonary fibrosis (OR = 5.7, 95% CI: 1.7, 19.5; P = 0.01) and sinus infections (OR = 2.7, 95% CI: 1.8, 4.2; P < 0.0001) recorded in the 3 years before diagnosis, but not before this. We also found former smoking, some medications and higher socio-economic status significantly, but less strongly, associated. Conclusion: We found novel long-term associations between GPA and pre-existing bronchiectasis and autoimmune diseases.